Revision of world Austroterobiinae and Parasaphodinae (Hymenoptera: Chalcidoidea: Pteromalidae), parasitoids of giant scales (Hemiptera: Coccoidea: Monophlebidae) - Mitroiu, Mircea-Dan (Zootaxa, 2017)
The world genera and species of Austroterobiinae and Parasaphodinae (Hymenoptera: Chalcidoidea: Pteromalidae) are revised. Austroterobia Girault includes eight valid species, of which five are described as new: A. achterbergi sp. nov., A. iceryae Bouček, A. gatesi sp. nov., A. heydoni sp. nov., A. maldica Narendran & Das, A. noyesi sp. nov., A. partibrunnea Girault, and A. partiviridis sp. nov. Teasienna Heydon includes five valid species, of which four are described as new: T. africana sp. nov., T. burksi sp. nov., T. eirene Heydon, T. gibsoni sp. nov., and T. heratyi sp. nov. Parasaphodes Schulz includes four valid species, of which one is described as new: P. afer sp. nov., P. flavipes (Ashmead) comb. nov., P. iceryae (Ashmead), and P. townsendi (Ashmead). Additionally, another new combination is proposed, Chrysolampus japonicus (Ashmead) comb. nov. The lectotypes of Parasaphodes flavipes and P. townsendi are designated. Teasienna males and the male of A. partibrunnea are described for the first time. The subfamily Austroterobiinae is recorded for the first time in the Neotropical region, while the subfamily Parasaphodinae is recorded for the first time in the Afrotropical region. All species with known biology are parasitoids of giant scales, especially Icerya Signoret (Hemiptera: Coccoidea: Monophlebidae), some of which are important agricultural pests.